2015
DOI: 10.1302/0301-620x.97b9.35227
|View full text |Cite
|
Sign up to set email alerts
|

Implant-associated mycobacterium tuberculosis infection following surgical management of fractures

Abstract: In this retrospective observational cohort study, we describe 17 patients out of 1775 treated for various fractures who developed mycobacterium tuberculosis (MTB) infection after surgery. The cohort comprised 15 men and two women with a mean age of 40 years (24 to 70). A total of ten fractures were open and seven were closed. Of these, seven patients underwent intramedullary nailing of a fracture of the long bone, seven had fractures fixed with plates, two with Kirschner-wires and screws, and one had a hemiart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This may not be the case in infections caused by multidrug‐resistant Gram‐negative bacilli or fungi. However, implant‐associated Mycobacterium tuberculosis infection is not considered as difficult‐to‐treat and has a good prognosis in this respect . Last but not least, the surgical intervention must target the best possible functional outcome.…”
Section: Implant‐associated Osteomyelitis Of Long Bonesmentioning
confidence: 99%
“…This may not be the case in infections caused by multidrug‐resistant Gram‐negative bacilli or fungi. However, implant‐associated Mycobacterium tuberculosis infection is not considered as difficult‐to‐treat and has a good prognosis in this respect . Last but not least, the surgical intervention must target the best possible functional outcome.…”
Section: Implant‐associated Osteomyelitis Of Long Bonesmentioning
confidence: 99%
“…[98][99][100] Mycobacterium tuberculosis 101,102 is rare even in endemic countries. 103 When atypical slow-growing pathogens are identified, a pre-existing bone infection, pathological fracture and an immunocompromised state must be suspected. [104][105][106][107]…”
Section: Microbiologymentioning
confidence: 99%
“…If a patient has a weakened immune system, tuberculosis can recur. Some studies have shown that M. tuberculosis in granulomas can be hematogenously spread to distant sites and that surgical trauma is conducive to colonization by these organisms 46,47 . Marmor reported a patient with osteoarthritis who demonstrated joint swelling, pain, and fever, 2 months after TKA; M. tuberculosis was cultured in the patient's joint fluid and blood 15 .…”
Section: Mechanism Of Tuberculosis Infection After Tkamentioning
confidence: 99%